Hepatitis C Attributable Healthcare Costs and Mortality among Immigrants: A Population-Based Matched Cohort Study - Aysegul Erman; Yeva Sahakyan; Karl Everett; Christina Greenaway; Naveed Janjua; Jeffrey C. Kwong; William W. L. Wong; Hong Lu; Beate Sander (Canadian Journal of Gastroenterology and Hepatology)
Background. Data on the economic burden of chronic hepatitis C (CHC) among immigrants are limited. Our objective was to estimate the CHC-attributable mortality and healthcare costs among immigrants in Ontario, Canada. Methods. We conducted a population-based matched cohort study among immigrants diagnosed with CHC between May 31, 2003, and December 31, 2018, using linked health administrative data. Immigrants with CHC (exposed) were matched 1 : 1 to immigrants without CHC (unexposed) using a combination of hard (index date, sex, and age) and propensity-score matching. Net costs (2020 Canadian dollars) collected from the healthcare payer perspective were calculated using a phase-of-care approach and used to estimate long-term costs adjusted for survival. Results. We matched 5,575 exposed individuals with unexposed controls, achieving a balanced match. The mean age was 47 years, and 52% was male. On average, 10.5% of exposed and 3.5% of unexposed individuals died 15 years postindex (relative risk = 2.9; 95% confidence interval (CI): 2.6–3.5). The net 30-day costs per person were $88 (95% CI: 55 to 122) for the prediagnosis, $324 (95% CI: 291 to 356) for the initial phase, $1,016 (95% CI: 900 to 1,132) for the late phase, and $975 (95% CI: −25 to 1,974) for the terminal phase. The mean net healthcare cost adjusted for survival at 15 years was $90,448. Conclusions. Compared to unexposed immigrants, immigrants infected with CHC have higher mortality rates and greater healthcare costs. These findings will support the planning of HCV elimination efforts among key risk groups in the province.